Pedagogical Mechanisms of Arabic Language Acquisition in Instagram-Based Microlearning: A Case Study of @guncelarapca - Muhammad Syafii Tampubolon; Ali Saif; Zaid Barzenji; Widiyanto Widiyanto; Zulkifli Hayad (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2026)
The increasing use of social media for educational purposes has created new opportunities for microlearning in language education. This study investigates the pedagogical mechanisms of Arabic instructional content published on the Instagram account @guncelarapca. Employing a qualitative case study design and content analysis approach, the research examined 74 instructional posts selected from 186 publications between January and June 2025. Data were collected through systematic digital observation and documentation of visual content, captions, hashtags, and engagement indicators, guided by Microlearning Theory, Second Language Acquisition, and Digital Pedagogy. The findings reveal that instructional content was delivered through static images, carousel posts, and short video reels, with vocabulary-focused materials dominating the dataset, followed by fixed expressions and semantic comparisons. The content consistently exhibited core microlearning characteristics, including brevity, a single instructional focus, limited informational density, and visual organization. Structurally, each post functioned as an independent, modular learning unit without evidence of sequential curriculum design or progressive pathways. User engagement was documented through platform-based metrics such as likes and comments, which reflect user interaction patterns rather than learning outcomes. This study contributes to digital language education literature by providing empirical documentation of how microlearning-oriented Arabic content is structured and disseminated on social media. The findings offer a descriptive foundation for future research examining learner experiences, instructional effectiveness, and language acquisition processes in social media-based environments